(3cJGH aj GdfcGMs
(3ChdgG (B:s
(3djSJ dg GeQCI abGdhG hEf cGf cKjQ GdeGd ? abGd hEf cGf hcGf QShd Gddg Udi Gddg Ydjg hSde hecGfg hEecGf s
(3BNQgG (B:s
(3fSCd Gddg JYGdi ef aVdg GdYah hGdYGajI hGdSdGeI hCf jNJe dfG HNjQ CLeYjf Bejf s
(3GdfSNI HgG MhGTs
(3GdfSNI efbhdI Yf fSNI HNW GdeDda ceG ai BNQgGs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdESdGejs